Implementation of The Class V B School Literacy Movement Program at SDN Bandungrejosari 3 Malang Using a Case Study Approach - Agustina, Yesica; Delawanti, Denna; Agus Setiawan, Dwi (Berpusi Publishing, 2024)
Current curriculum changes have an impact on the world of education, namely the creation of a new movement with the School Literacy Movement (GLS). The school literacy movement is an effort made to create a learning organization whose citizens are lifelong literate and involve the public. The problems that occur at SDN Bandungrejosari 3 Malang are students' low interest in reading, the three stages of literacy are less than optimal, students must be reminded to carry out literacy activities. The aim of this research is to determine the implementation of the Literacy Movement (GLS) program at SDN Bandungrejoasi 3 Malang. This research uses qualitative research and the type of research uses case studies with research instruments in the form of observation sheets, interviews and documentation sheets. The research subjects were school principals, teachers, class V B students, and librarians. The research results show that SDN Bandungrejosari 3 Malang has implemented the School Literacy Movement (GLS) program based on government policy and school policy. The GLS program has three stages, namely the habituation, development and learning stages. The GLS program running at SDN Bandungrejosari 3 Malang includes library visits, learning outside the classroom, decorating wall panels and arranging reading corners.